Istota modelowania procesów adaptacji systemów informacyjnych zarządzania - Skwarnik, Marek (The nature of MIS adaptation process modelling, 2005)
The article presents MIS changes area, in which appropriate adjustment (adaptation) procedures and tools should be used. The first section focuses on business oriented reactive changes (basic environment of MIS). The one next describes IS adaptation processes, responding to these changes. The third section refers to purposes and domain of adaptation process modeling. Particularly it focuses on a detailed and multitopic description of processes, adaptation effects and MIS changed elements. In conclusion we propose detailed issues for successive MIS adaptation research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 169-177